Litter, Nutrient Dynamics and forest Floor Management in Sal and Miscellaneous forests of Satpura Plateau (India) - Patra, A. K.; Pande, P. K. (Indian Forester, 2012)
The paper presents a comparative account of litter fall, litter nutrient concentration, return and release in open miscellaneous forest (CMF, site-I), closed miscellaneous forest (CMF, site-II), open sal (OSF, site-III) and closed sal (CSF, site-IV) and also between miscellaneous (MF) and sal forests (SF) of tropical dry deciduous mixed and tropical dry sal forests of Satpura plateau, Madhya Pradesh (India). Leaf and litter fall was erratic in miscellaneous forest (sites I, II) and peak period was in December while peak leaf fall period in sal forest was March-June. However, fall was unimodal in sal forest (sites III, IV). The magnitude of annual leaf fall (kg ha-1) followed the order: 20958.40 (site-III) > 18708.60 (site-IV) > 3381.71 (site-II) > 2897.60 (site-I). The higher leaf and litter fall in OSF than of CSF is related to the higher dominance of the deciduous species Tectona grandis in the stand and also higher age of the stand. Litter decomposition rate (k) was higher for sal forest (SF) than the miscellaneous forest (SF). Generally, Ca and N were higher than K, Mg and P in all litter fractions, irrespective of sites. Variance ratio (F) test showed that SF showed higher values of nutrient concentration and their lower variations as compared to MF. Open forests showed lower concentrations of nutrient than closed forests.